2019
DOI: 10.20473/j.djmkg.v52.i4.p219-223
|View full text |Cite
|
Sign up to set email alerts
|

The potency of Andrographis paniculata Nees extract to increase the viability of monocytes following exposure to Porphyromonas gingivalis

Abstract: Background: Periodontitis is a chronic infectious disease affecting the global population. In Indonesia, the prevalence of periodontal disease has reached 57.6% across all age groups. The bacterium considered as the orginator factor of periodontitis is Porphyromonas gingivalis (P. gingivalis). Herbal ingredients are currently being promoted as a form of treatment because of the minimal side effects they induce. Andrographis paniculata Nees (ApN) extract produces pharmacological effects, including ones immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, that does not mean that gram-negative bacteria's growth in supragingival plaques cannot be inhibited, only in more significant duration and concentration. [24][25][26] The cell viability test, which is a test to measure cell life's ability by calculating the number of living cells, supports the inhibitory impact of lemongrass extract against supragingival plaque bacteria in gingivitis patients. It is exposed to the material and to be tested by Methyl Thiazolyl Tetrazolium (MTT) assay method read using Enzyme-Linked Immunoassay (ELISA) Reader absorbent.…”
Section: Table 6: Post-hoc Test With Games-howell Testmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that does not mean that gram-negative bacteria's growth in supragingival plaques cannot be inhibited, only in more significant duration and concentration. [24][25][26] The cell viability test, which is a test to measure cell life's ability by calculating the number of living cells, supports the inhibitory impact of lemongrass extract against supragingival plaque bacteria in gingivitis patients. It is exposed to the material and to be tested by Methyl Thiazolyl Tetrazolium (MTT) assay method read using Enzyme-Linked Immunoassay (ELISA) Reader absorbent.…”
Section: Table 6: Post-hoc Test With Games-howell Testmentioning
confidence: 99%
“…High absorption values indicate many living cells, whereas low absorbance values indicate a small number of living cells. [26,27] In 2018, cell viability experiments revealed that a 100% concentration of lemongrass extract with a live cell percentage of 100.41% could preserve the viability of fibroblasts Baby Hamster Kidney-21 (BHK-21) cells. The research of lemongrass plant extract and viability of living cells are expected to be a reference for further research.…”
Section: Table 6: Post-hoc Test With Games-howell Testmentioning
confidence: 99%